New Challenges After COVID-19 and Turkiye's Response - ÖZGÜR, EMRE (İstanbul Kültür Üniversitesi, 2022)
Every age has its own phenomenon that shape the world order. In the medieval period, it was religion. In the enlightenment, it was science. In the nineteenth and twentieth centuries, it was the rise of nationalism. In our age, developments in communication (most notably the internet) and transportation make globalization a critical concept. Especially with the Covid-19 pandemic, the advantages and disadvantages of globalization have become a hot topic. Whether or not we are on the verge of a new world order is on the agenda of academicians, researchers, strategy experts and policymakers. The President of the USA, Joe Biden, said that there's going to be a new world order and his country has to lead it. When the pandemic broke out, Chinese President Xi Jinping highlighted that from now on, the international community has to see humanity as one community. Also, Türkiye's President, Recep Tayyip Erdoğan, emphasized that the world order will not be the same after the pandemic and the notion of state will evolve accordingly to today's needs. This study tries to explain different world orders in the past and the direction of the change in today's world. The reasons behind Türkiye's new economic and political paradigms and the way it adapts to today's conjuncture are analysed.
Covid-19 Sonrası Yeni Zorluklar ve Türkiye'nin Cevabı
▪ Yüksek lisans tezi.
Keywords: Globalization; New World Order; Covid-19; Security